The Impact of Corruption on the Economic Security of the State - MAZARAKI, Anatoly; MELNYK, Tetiana; SEROVA, Lyudmila (Theoretical and Practical Research in Economic Fields, 2023)
The level of national economic security is influenced by many factors. But over the past year and a half, Ukraine has faced new challenges and threats of an unprecedented blow to its economic security from the armed aggression of the Russian Federation. In addition to the above-mentioned threats to Ukraine's economic security, "old" internal problems, one of which is corruption, have had a significant negative impact. Summarizing domestic and foreign scientific theories and empirical studies, the article analyzes the main elements of corruption's impact on economic security and identifies the direct and indirect impact of corruption on economic growth. It is argued that corruption has increased the challenges to the country's economic security due to: a decrease in total investment and a slowdown in economic growth, a reduction in spending on education and health care, a deterioration of infrastructure and taxation, and a decrease in foreign direct investment. The author concludes that it is necessary to systematically develop and implement measures to prevent and combat economic corruption. At the same time, achieving economic security should be an attribute and integral part of the national anti-corruption policy.